Human Genetics Society of Australasia Position Statement: Population-Based Carrier Screening for Cystic Fibrosis. (28th November 2014) - Delatycki, Martin B.; Burke, Jo; Christie, Louise; Collins, Felicity; Gabbett, Michael; George, Peter; Haan, Eric; Ioannou, Liane; Martin, Nicole; McKenzie, Fiona; O'Leary, Peter; Scoble-Williams, Nicole; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Since the discovery in 1989 that mutations in cystic fibrosis transmembrane conductance regulator (CFTR) underlie cystic fibrosis (CF), the most common life shortening genetic disorder in Caucasians, it has been possible to identify heterozygous mutation carriers at risk of having affected children. The Human Genetics Society of Australasia has produced a position statement with recommendations in relation to population-based screening for CF. These include: (1) that screening should be offered to all relatives of people with or carriers of CF (cascade testing) as well as to all couples planning to have children or who are pregnant; (2) the minimum CFTR mutation panel to be tested consists of 17 mutations which are those mutations that are associated with typical CF and occur with a frequency of 0.1% or higher among individuals diagnosed with CF in Australasia; (3) that genetic counselling is offered to all couples where both members are known to have one or two CFTR mutations and that such couples are given the opportunity to meet with a physician with expertise in the management of CF as well as a family/individual affected by the condition.